2007
DOI: 10.1007/s00221-007-1055-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motor preparation and spatial attention on corticospinal excitability in a delayed-response paradigm

Abstract: The preparation of motor responses during the delay period of an instructed delay task is associated with sustained neural Wring in the primate premotor cortex. It remains unclear how and when such preparation-related premotor activity inXuences the motor output system. In this study, we tested modulation of corticospinal excitability using single-pulse transcranial magnetic stimulation (TMS) during a delayed-response task. At the beginning of the delay interval participants were either provided with no inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 15 publications
(21 reference statements)
6
47
1
Order By: Relevance
“…In contrast, the selected condition was associated with a particularly weak MEP suppression; it was much less pronounced than in the non-selected condition. In the past, a few studies have reported an increase in MEP amplitudes during delay periods [12, 20, 21]. Interestingly, all of them required participants to provide their response by pressing a button.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the selected condition was associated with a particularly weak MEP suppression; it was much less pronounced than in the non-selected condition. In the past, a few studies have reported an increase in MEP amplitudes during delay periods [12, 20, 21]. Interestingly, all of them required participants to provide their response by pressing a button.…”
Section: Discussionmentioning
confidence: 99%
“…Activation decreases in these regions are almost exclusively in the ‘planning versus baseline’ contrast, are in line with our previous findings (den Braber et al ., 2008) and those from van den Heuvel and colleagues (2005). Since these areas are involved in basic functions of motion processing (Rowe et al ., 2001), motor preparation (Hoshi and Tanji, 2000; Mars et al ., 2007) and visuospatial processing (Cabeza and Nyberg, 2000), they may support mainly proper task execution (e.g. analysis of planning stimulus, imaginary movement of the beads, executing a response) rather than higher order planning.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that this early reduction reflects the proactive inhibition of an undesirable response (Koch et al, 2006;Mars et al, 2007;van den Hurk et al, 2007;van Elswijk et al, 2007), such as an avoidance movement elicited by the approaching ball. We therefore measured the effect of voluntary inhibition of the motor response at the time of distractor presentation (Coxon et al, 2006(Coxon et al, , 2007 to examine whether this would suppress MEP amplitudes to a similar level as found with near distractor balls.…”
Section: Experiments 3: Near Distractor Balls Suppress Corticospinal Ementioning
confidence: 99%
“…We further examined the process of "proactive inhibition," the ability to inhibit in advance one movement to execute another (Koch et al, 2006;Mars et al, 2007;van den Hurk et al, 2007;van Elswijk et al, 2007), in relation to the suppression of possible avoidance responses elicited by the approaching ball.…”
Section: Introductionmentioning
confidence: 99%